Pemberdayaan Ekonomi Masyarakat Desa Gegarang melalui Pelatihan Pembuatan dan Pengemasan Kerupuk Berbahan Dasar Ikan Depik - Ayu Rahma Nengsi; Didi Sartika (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
In the field of community economic empowerment, we found that the Gegarang village in Bintang District, Central Aceh Regency has abundant natural resources, rich in lake products in the form of depik fish, lake lobster and various other lake animals which have high economic value if further processing is carried out. carry on. However, the potential of natural resources owned has not been supported by strong economic institutions in terms of management, human resources, capital, and access to penetrate the market so that it has not had a significant influence on the community's economy. Therefore, our service team held a training in order to improve the human resources of the local community, to be more creative in processing available natural resources in an effort to improve their standard of living and economy. Training on making crackers using depik fish as the main ingredient and packaging of depik fish. In this case, we are working with the BUMK of Gegarang village. The method used in this research is PAR Participatory Action Research. This training ran smoothly, the community was trained to process raw materials into finished goods, so that their economic value would increase. This training received appreciation and support from various agencies such as the food, tourism and fisheries services. During the training, all units and communities involved were very enthusiastic and very interested. Responding to the enthusiasm of the community, the local sub-district included them on a stand at the Creative Economy and MSME Week event organized by the Central Aceh District Office in April 2022. As a result, Gegarang Village was ranked first as the best selling product that penetrated 500 peaces, and for the time being This depik cracker has already reached the national level marketing. Keywords: Economic Empowerment, Packaging Training, Crackers Depik Introduction